Flooding and its impacts on Nkondo community in Rundu, Kavango east region of Namibia, 1950s - Likuwa, Kletus M. (Jamba, 2016)
This is a study on flooding and its impact on the Nkondo community in Rundu, in the Kavango area of Namibia. It draws from archival sources at the National Archives of Namibia. Whilst archival documents provide an idea of what and how colonial officials thought of and related to the colonial subjects, they cannot represent the feelings, beliefs and interpersonal relationships of the ordinary people. This article thus made use of oral interviewing, not as a means to fill the gap but as an alternative to exploring memories of former Nkondo residents about the 1950s flood and its impact. Interviews were carried out in 2004 and 2005 when 14 people were interviewed for the histories of forced removals in Rundu, but only five are used for this article as they specifically speak to the story of flooding. Interviewees were chosen through referrals from the headmen of the surrounding villages of Rundu. Interviewees were asked questions that provide a chronological representation of a case study of forced relocations in Rundu. The article is an important historical piece that draws on unique oral-history regarding flooding and its impact. Furthermore, it is a story about power, politics and colonial dynamics and forced relocation using flooding as a pretext. The article indicates how colonial authorities made use of this benevolent excuse of a natural disaster to compel people to move permanently to new areas so as to fulfil the colonial administration’s political agenda of security and control over the population. The article indicates that flood-prone communities may fear relocating permanently due to cultural, social and economic factors. Thus, the government should not use force to relocate communities but should address communities’ fears and provide them with support in relocated areas.